Synthesis of recyclable, chemically cross-linked, high toughness, high conductivity ion gels by sequential triblock copolymer self-assembly and disulfide bond cross-linking1. Issue 29 (27th April 2015) - Wei, Chengsha; Chen, Mingming; Liu, Dong; Zhou, Weiming; Khan, Majid; Wu, Xibo; Huang, Ningdong; Li, Liangbin
<x xml:space="preserve">Abstract</x> We reported the synthesis of a high toughness, high conductivity ion gels by a sequential triblock copolymer self-assembly and disulfide bond cross-linking, combining the high toughness of chemical with recyclability of physical cross-linking ones.